From psychogenic movement disorder to functional movement disorder: It's time to change the name - Edwards, Mark J.; Stone, Jon; Lang, Anthony E. (Movement disorders, 2014)
ABSTRACT Successive attempts at rebranding may be behind at least some of the proliferation of terms we have at our disposal when describing patients with what are now most often referred to as “psychogenic,” “conversion,” or “somatoform” symptoms. The most popular term in the movement disorder literature, “psychogenic,” provides the aetiology of the disorder within the name, indicating that the symptoms are “born of the mind.” Here we argue that it is logical to stop using a term that defines the disorder with regard to a poorly defined aetiology that is not supported by current evidence, and, instead, to use a broad term—functional—not as a “polite eponym” but as a term that is freer from such assumptions and does not reinforce dualistic thinking. The main argument for change is not political or even practical, but scientific. © 2013 International Parkinson and Movement Disorder Society